4
$\begingroup$

Suppose a function $f:(-a,a)-\{0\}\rightarrow(0,\infty)$ satisfies $\lim\limits_{x\rightarrow 0}\left(f(x)+\frac{1}{f(x)}\right)=2$. Show that $$\lim\limits_{x\rightarrow 0}f(x)=1$$


Let $\epsilon>0$ , then there exists a $\delta>0$ such that $$\left(f(x)+\frac{1}{f(x)}\right)-2<\epsilon\;\;\;\text{and}\;\;\;|x|<\delta$$

Then

\begin{align} &\left(f(x)+\frac{1}{f(x)}\right)-2\\ =&\left(f(x)-1\right) +\left(\frac{1}{f(x)}-1\right)<\epsilon\tag{1} \end{align}

Squaring $(1)$ both sides gives $$\left(\left(f(x)-1\right) +\left(\frac{1}{f(x)}-1\right)\right)^2<\epsilon^2\tag{2}$$

Since $(f(x)-1)^2\leq\left(\left(f(x)-1\right) +\left(\frac{1}{f(x)}-1\right)\right)^2$, by using $(2)$, $(f(x)-1)^2<\epsilon^2\Rightarrow f(x)-1<\epsilon$; therefore, as $\epsilon$ is arbitrary, $\lim\limits_{x\rightarrow 0}f(x)=1$


Can someone give me a hint to do this question without using epsilon-delta definition? Thanks

$\endgroup$
1
$\begingroup$

Since $f$ is positive and $f + (1/f)$ tends to $2$ as $x \to 0$, it follows that $f$ is bounded and away from $0$ as $x \to 0$ . Therefore it follows that $\sqrt{f(x)}$ is bounded and away from $0$ as $x \to 0$. Now we can see that $$f(x) + \frac{1}{f(x)} = \left(\sqrt{f(x)} - \frac{1}{\sqrt{f(x)}}\right)^{2} + 2$$ and therefore $$\frac{(f(x) - 1)^{2}}{f(x)} \to 0$$ so that $(f(x) - 1)^{2} \to 0$ and therefore $|f(x) - 1| \to 0$ and then $f(x) \to 1$.

$\endgroup$
1
$\begingroup$

Define $h(u) = \frac{u + \sqrt{u^2 - 4}}{2}$ (this is the inverse function of $x \mapsto x + \frac{1}{x}$). Note that $h(2) = 1$ and that $h$ is continuous at $u = 2$. Thus,

$$ 1 = \lim_{u \to 2} h(u) = \lim_{x \to 0} h \left( f(x) + \frac{1}{f(x)} \right) = \lim_{x \to 0} \frac{f(x) + \frac{1}{f(x)} + \sqrt{\left( f(x) + \frac{1}{f(x)} \right)^2 - 4}}{2} = \lim_{x \to 0} \frac{f(x) + \frac{1}{f(x)} + \sqrt{ \left( f(x) - \frac{1}{f(x)} \right)^2}}{2} = 1 + \lim_{x \to 0} \left| f(x) - \frac{1}{f(x)} \right| $$

which implies that

$$\lim_{x \to 0} \left( f(x) - \frac{1}{f(x)} \right) = 0. $$

Combining both results together we have

$$ 2 = 2 + 0 = \lim_{x \to 0} \left( f(x) + \frac{1}{f(x)} \right) + \lim_{x \to 0} \left( f(x) - \frac{1}{f(x)} \right) = \lim_{x \to 0} 2f(x) $$

which implies that $\lim_{x \to 0} f(x) = 1$.

$\endgroup$
  • $\begingroup$ Yes, isn't it what's written? $\endgroup$ – levap Dec 8 '15 at 13:20
  • $\begingroup$ Thank you! I somehow completely failed to see it. $\endgroup$ – levap Dec 8 '15 at 13:49
1
$\begingroup$

$$ a + \frac 1 a = \left( a - 2 + \frac 1 a \right) +2 = \left( \sqrt a - \frac 1 {\sqrt a} \right)^2 + 2 = \text{square} + 2. $$ So this is $\ge 2$ unless the square is $0$.

$a+ \dfrac 1 a$ cannot get close to $2$ unless $a$ gets close to $1$.

Even if you allow complex numbers (so that the inequality above doesn't hold), we have $$ a + \frac 1 a = 2 \Longrightarrow a^2 + 1 = 2a $$ and that is a quadratic equation whose only solution is $a=1$ (a double root).

$\endgroup$
  • $\begingroup$ $a = 2$ is not a root of the equation. you probably meant $a = 1$ $\endgroup$ – Netivolu Feb 7 '18 at 10:06
0
$\begingroup$

Generalization: Suppose $f:(-a,a) \setminus \{0\} \to (0,\infty)$ and $g: (0,\infty)\to \mathbb R.$ Let $y_0> 0.$ Assume $g$ is strictly decreasing on $(0,y_0],$ and strictly increasing on $[y_0,\infty).$ If $\lim_{x\to 0} g(f(x)) = g(y_0),$ then $\lim_{x\to 0} f(x) = y_0.$

This applies to the problem at hand by letting $g(y) = y + 1/y$ with $y_0 = 1.$

Sketch of proof: Suppose $\limsup_{x\to 0} f(x) > y_0.$ Then there exists $z>y_0$ and a sequence $x_n \to 0$ such that $f(x_n)> z$ for all $n.$ This implies $g(f(x_n))> g(z)$ for all $n.$ Because $g(z) > g(y_0),$ this is a contradiction. Thus $\limsup_{x\to 0} f(x) \le y_0.$ Same idea if $\liminf_{x\to 0} f(x) < y_0.$ Thus

$$y_0 \le \liminf_{x\to 0} f(x)\le \limsup_{x\to 0} f(x)\le y_0,$$

giving the result.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.